Analysis of graphical user interfaces of music services taking into account universal design principles - Damian Mydlak; Kacper Adamiak; Maria Skublewska-Paszkowska (Journal of Computer Sciences Institute)
While creating services, great emphasis is placed on usability and accessibility of the user interface. These elements allow applications to reach the widest possible audience. The purpose of this study was to examine the impact of contrast, font size and Universal Design principles on the usability of music services. The evaluations were carried out with the help of two applications, first that meets and second that does not meet WCAG 2.1 and Universal Design principles. Using eye tracking technology, LUT and SUS surveys and the WAVE tool. Twenty-one participants took part in the eye tracker study. Comparative factors were average times to first fixation, number of fixations and survey results. The results showed that the use of Universal Design principles and WCAG 2.1 has a significant impact on the accessibility and usability of applications.